The timing of antenatal care access for adolescent pregnancies in Cape Town, South Africa - Anja Smith; Grace Leach; Laura Rossouw (AOSIS, 2024)
Background: Late antenatal care (ANC)-seeking among pregnant adolescents threatens their health outcomes, and the health outcomes of their new-borns. South Africa has experienced a rapid increase in adolescent pregnancies during the COVID-19 pandemic, adding to the existing concerns around adolescent pregnancy care-seeking behaviour. Aim: The main aim of this study was to investigate the causes and covariates of late ANC access among adolescents in the Cape Town Metropole, South Africa. Setting: Three public healthcare facilities in the Cape Town Metropole, 2018-2019. Methods: A retrospective, cross-sectional study on ANC seeking behaviour was conducted, surveying 202 adolescents. Late attendance was defined as attending ≥ 3 months. For this study, adolescents were defined as women aged 16-18 years. The sample was restricted to adolescents who used public healthcare facilities or who did not attend at all. Data were analysed using univariate, bivariate and multivariate methods. Results: A total of 50.8% (n = 99/195) of the pregnant adolescents in the sample had their first ANC visit 3 months. 14.9% (n = 29/195) did not attend at all. Major contributors to delayed care-seeking include poor pregnancy identification (n = 45/99, 45.5%), and a lack of information about ANC. Age, education, and alcohol consumption were significant predictors of delayed care-seeking. Conclusion: Delayed ANC attendance contributes to negative long-term health outcomes for pregnant adolescents and their new-borns. Improving access to pregnancy tests in the public sector could benefit adolescents with earlier pregnancy identification. Adolescents need to be made aware of their care seeking options. Contribution: There is evidence of long-term health impacts of late ANC attendance by pregnant adolescents, but there is an absence of evidence on the timing and barriers of late care-seeking behaviour. In this study, late ANC attendance among adolescents was associated with late pregnancy identification and poor knowledge of care options.